SANCTIONS AS A TOOL FOR ENFORCING THE INTERNATIONAL LEGAL RESPONSIBILITY OF STATES FOR INTERNATIONAL LAW VIOLATIONS - Proshchaev, Volodymyr; Biletskyi, Yevhenii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
Purpose: to analyse the nature of international sanctions as an instrument for enforcing the international legal responsibility of states, to clarify their relationship with other legal categories (in particular countermeasures) and to determine their role in changing the behaviour of offending states in order to restore international legal order. Research methods: the article uses a set of scientific methods: semantic and linguistic analysis (to reveal the meaning of the concepts of ‘instrument’, “means” and ‘technique’ through dictionary definitions); comparative legal method (to compare the regimes of international sanctions (centralised measures of organisations) and countermeasures (decentralised actions of states); functional analysis (to study sanctions as a mechanism for managing foreign policy risks and changing the incentive system of the offending state); theoretical and prognostic method (to justify the need for further research in the context of human rights protection and the effectiveness of ‘targeted’ measures). Results: it has been established that sanctions in international public law are an instrument of direct influence on the behaviour of a state, ensuring the restoration of the violated rights of subjects; conceptual uncertainty has been identified in national doctrine as to whether sanctions are a separate legal institution or an integral part of the institution of international legal responsibility; it has been determined that the main mechanism of influence of sanctions is to increase the ‘cost’ of undesirable behaviour by the offending state; it has been argued that the effectiveness of coercion in contemporary law depends on the transition to ‘targeted’ (purposeful) sanctions against specific individuals or sectors of the economy in order to minimise humanitarian consequences. Discussion: the article engages in a scientific debate on the distinction between sanctions and countermeasures: sanctions are interpreted as collective coercion by international organisations, while countermeasures are interpreted as a form of self-help by individual states. Particular attention is paid to the danger of the impact of general sanctions on the civilian population and human rights, especially in authoritarian regimes. The authors emphasize the lack of a unified approach to defining the concept of ‘sanctions’ in legislation and doctrine, which requires an update of scientific views taking into account the current state of the international legal order.